1995
DOI: 10.1093/infdis/172.5.1397
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interaction of Escherichia coli 0157:H7-Derived Shiga-like Toxin II with Human Renal Endothelial Cells

Abstract: In Escherichia coli O157:H7 foodborne infections of humans, the Shiga-like toxins (SLTs) are thought to be the cause of life-threatening vascular complications, including acute renal disease known as hemolytic uremic syndrome or HUS. As virtually all E. coli O157:H7 isolates from HUS patients produce SLT-II (vs. SLT-I), the possible preferential interaction of SLT-II with human renal microvascular endothelial cells (HRMEC), the putative target of the SLTs in the development of HUS, was studied. SLT-II was 1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
126
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(136 citation statements)
references
References 13 publications
7
126
0
3
Order By: Relevance
“…Surface plasmon resonance analysis showed that Stx-1 easily binds to and detaches from Gb3, in contrast to Stx-2, which binds slowly but also dissociates very slowly, thus staying on the cells long enough to be incorporated (62). The latter could explain why Stx-2 is 1000-fold more toxic than Stx-1 on human endothelial cells in vitro (63).…”
Section: Shiga Toxin or Shiga Toxins?mentioning
confidence: 99%
“…Surface plasmon resonance analysis showed that Stx-1 easily binds to and detaches from Gb3, in contrast to Stx-2, which binds slowly but also dissociates very slowly, thus staying on the cells long enough to be incorporated (62). The latter could explain why Stx-2 is 1000-fold more toxic than Stx-1 on human endothelial cells in vitro (63).…”
Section: Shiga Toxin or Shiga Toxins?mentioning
confidence: 99%
“…Epidemiological studies, together with in vivo and in vitro experiments, have revealed that stx2 (and its variants) is the most important virulence factor associated with severe human disease. STEC producing stx2 is more commonly associated with serious disease than isolates producing stx1 or stx1 plus stx2 (Boerlin et al, 1999;Louise & Obrig, 1995;Paton & Paton, 1998). In the current study, the majority of strains were stx1-producing strains (24/29, 83 %); only 5/29 (17 %) strains carried stx2.…”
Section: Distribution Of Virulence Genesmentioning
confidence: 99%
“…Epidemiological studies, together with in vivo and in vitro experiments, have revealed that Stx2 is the most important virulence factor associated with severe human disease. Indeed, Stx2 is 1000 times more cytotoxic than Stx1 towards human renal endothelial cells, and STEC producing Stx2 are more commonly associated with serious diseases than isolates producing Stx1 or Stx1 plus Stx2 (Louise & Obrig, 1995;Boerlin et al, 1999;Paton & Paton, 1998). Several Stx2 variants have been identified on the basis of sequence homology and immunological crossreactivity (Ito et al, 1990;Schmitt et al, 1991;Paton et al, 1995;Friedrich et al, 2002;Pierard et al, 1998).…”
Section: Introductionmentioning
confidence: 99%